Penerapan Pendekatan Pembelajaran Berdiferensiasi dalam Mendukung Kebutuhan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam (PAI) Kelas X Phytagoras di SMAN 2 Sangatta Utara - Ema Pariati; Anjani Putri Belewati Pandiangan; Siti Munfiatik (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Differentiated learning approach aims to find out how the application of differentiated learning approach supports students' learning needs in Islamic Religious Education (PAI) subjects for Class X Phytagoras at SMAN 2 Sangatta Utara and what are the advantages and disadvantages of implementing a differentiated learning approach in supporting students' learning needs in Islamic Religious Education (PAI) subjects for Class X Phytagoras at SMAN 2 Sangatta Utara. This study uses a qualitative method, with a descriptive type. Using data sources in the form of primary data and secondary data, the informants are PAI teachers and two students. Researchers use data collection techniques in the form of observation, interviews, document studies and data analysis. The results of this study indicate that the application of a differentiated learning approach in supporting students' learning needs at SMA Negeri 2 Sangatta Utara. 1. Improving student learning outcomes is better with interesting learning where teachers explain and provide assignment choices that are in accordance with students' wishes. 2. Active participation of students in the learning process increased, with 80% of students showing activeness in the classroom in the process of working on assignments carried out by groups or individuals. 3. Teachers need more time because before students do assignments, teachers must provide material first at the beginning of learning. The results of this study indicate that a differentiated learning approach can be an alternative in supporting the diverse learning needs of students.